PENINGKATAN HASIL BELAJAR DAN KETERAMPILAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING(PBL) BERBANTUAN KOTAK HITAM PUTIH - Fatimah, Wike; Slameto, Slameto; Setyaningtyas, Eunice Widyanti (KALAM CENDEKIA PGSD KEBUMEN, 2018)
AbstractThis study is aimed to find out the improvement of students learning result and problem solving skill in Mathematic subject by the appliance of PBL (Problem Based Learning) method to the fifth grade elementary school students. In this research, the researcher used CAR (Classroom Action Research) method that bring about of two cycles. Each cycle consists of planning, action, observation, and reflection. The subject of this research is the fifth grade elementary school students. The Data analysis is carried out by using comparative descriptive analysis. It shows that there is improvement from the students cognitive result, from 71,42 % up to 89,29%, it means the students result improve up to 17,87%.  The result of students problem solving skill in mathematic subject improves from 70,86% to 90,28% and to the students affective result, there is improvement on their behavior become much better, and the student?s mindset become more advance, the student is able to work together with their friends to solve their problem, and become more courageous to ask and share their ideas. From the result, it could be concluded that the using of PBL (Problem Based Learning) with the helping of white and black box could improve student?s learning result and problem solving skill in Mathematic subject.Keywords:  Problem Based Learning (PBL), black and white box, learning result, problem solving skill in Mathematic subject AbstrakPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar dan keterampilan pemecahan masalah Matematika dengan penerapan model pembelajaran Problem Based Learning(PBL)berbantuan kotak hitam putihpada siswa SD kelas IV. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus.Tiap siklus terdiri dari perencanaan, pelaksanaan, tindakan, observasi dan refleksi.Subjek penelitian ini terdiri dari siswa kelas IV Sekolah Dasar.Analisis data dilakukan dengan menggunakan analisis deskriptif komparatif. Hasil penelitian menunjukkan bahwa terjadi peningkatan hasil belajar kognitif dari 71,42% meningkat menjadi 89,29% untuk itu terjadi peningkatan sebesar 17,87%. Hasil belajar keterampilan pemecahan masalah matematika dari 70,86% menjadi 90,28% dan hasil belajar afektif terjadi peningkatan pada perilaku siswa yang lebih baik, pola pikir siswa menjadi lebih berkembang, siswa mampu bekerjasama dalam pemecahan masalah dan lebih berani bertanya serta mengungkapkan gagasanya. Jadi dapat disimpulkan bahwa penerapan model pembelajaranProblem Based Learning (PBL) berbantuan kotak hitam putih dapat meningkatkan hasil belajar dan keterampilan pemecahan masalah matematika.Kata kunci: Problem Based Learning, hitam putih, hasil belajar, keterampilan pemecahan masalah Matematika